Association between public health nurses' involvement in local healthcare planning and the corresponding off‐the‐job training - Kyoko Yoshioka‐Maeda; Misa Shiomi; Takafumi Katayama; Noriko Hosoya; Hitoshi Fujii; Tatsushi Mayama (Wiley, 2023)
Abstract Objective This study investigated the association between receiving off‐the‐job training and the involvement of public health nurses in local healthcare planning. Design A nationwide, cross‐sectional study design. Methods We sent self‐report questionnaires to 2,185 public health nurses with experience in developing local healthcare plans in Japan since 2013 and collected information related to three main categories: demographic data, involvement in local healthcare planning and strategies for healthcare planning. Results We received 1,281 responses (return rate of 58.6%), of which 231 did not meet the inclusion criteria. Thus, we analysed 1,050 valid responses. Among the 1,050 respondents, 496 (47.2%) had received off‐the‐job training in healthcare planning. A subsequent logistic regression analysis revealed that the following factors were associated with this achievement: holding a managerial position, receiving healthcare planning education at the undergraduate level, having mentors regarding the promotion of it, partially conducting cross‐sectional coordination and conducting groupwork with community‐dwelling residents.